The Use of PR Tools and Analysis of Their Effectiveness as Viewed by Managers of Czech Chemical Companies - Jelínková, Martina; Lošťáková, Hana; Macháčková, Kateřina (Univerzita Hradec Králové, 2021)
The paper presents the results of primary quantitative research aimed at determining the degree of use of various PR tools and evaluating their perceived effectiveness with the public. The respondents were managers of chemical industrial companies in the Czech Republic. It compares the use and perceived effectiveness of the monitored PR tools and identifies those that should be maintained, those that need to be developed and also those that should be restrained. This provides managers with a suitable guide for effective management of PR communication. The findings are supplemented by an analysis of differences in the use of monitored PR tools by the size of companies and differences in the perception of the effectiveness of the monitored PR tools according to different characteristics of respondents. It was confirmed that PR tools aimed at the public are used to a greater extent by larger companies (more than 250 employees) and respondents' views differ the most in the perceived effectiveness of press releases.
Využívání různých nástrojů PR a analýza jejich účinnosti pro ovlivňování veřejnosti dle názoru manažerů českých chemických podniků
Keywords: public relations; PR tools; influencing the public; chemical industry; public relations; nástroje PR; ovlivňování veřejnosti; chemický průmysl